The Effectiveness of Person-Centered Therapy in Individual Counseling for Adolescents Experiencing Trauma from Romantic Relationships - Fazar, Khaliza Nur; Sinaga, M. Harwansyah Putra (Ilomata International Journal of Social Science, 2024)
The purpose of this study is to determine the effectiveness of individual counseling with a person-centered approach to adolescents who have trauma due to romantic relationships, while the population studied of adolescents who have trauma due to romantic relationships who are not in a relationship from 10 samples that are given a scale of trauma due to romantic relationships as a pre-test are taken 5 samples with the highest scores. This study uses a quantitative method with a One-group Pretest-posttest Research Design. The method of the results of the study revealed that the reduction of trauma experienced by clients by 20.2% with the evidence of the results of the psychological scale provided so that individual counseling with a person-centered therapy approach can be declared effective in reducing trauma in adolescents due to romantic relationships.